Perspektif Guru dan Siswa : Penerapan Kurikulum Merdeka di Sekolah Dasar - Afridha Laily Alindra; Salsabilla Suci Attalia; Meilisa Meilisa; Gandes Rahmi Mahayun Sari; Dias Marisa; Saofa Salsa Safariyah; Nada Savaira Raihana; Tria Kurnia Sari (Badan Penerbit STIEPARI Press, 2025)
Along with the development of the times, the Indonesian curriculum continues to change. Indonesia has experienced curriculum changes starting from the 1947 curriculum to the 2022 curriculum, namely the Merdeka Curriculum. This study aims to determine the perspectives of teachers and students: the implementation of the Merdeka curriculum in elementary schools. This study uses a qualitative method. This research technique uses data collection in the form of observation, interviews, and questionnaires. This research was conducted at Purwakarta Elementary School, precisely at SDN 3 Sindangkasih. The informants in this study were the principal and 2 teachers at SDN 3 Sindangkasih. The results of the interview showed that the implementation of the Merdeka curriculum in elementary schools in Purwakarta was in accordance with the Merdeka Curriculum concept where the Merdeka Curriculum focuses on developing students' talents and interests and providing freedom in the learning process.